2022
DOI: 10.1177/01945998211068822
|View full text |Cite
|
Sign up to set email alerts
|

Rural Otolaryngology Care Disparities: A Scoping Review

Abstract: Objective To broadly synthesize the literature regarding rural health disparities in otolaryngology, categorize findings, and identify research gaps to stimulate future work. Study Design Scoping review. Data Sources A comprehensive literature search was performed in the following databases: PubMed/MEDLINE, Scopus, Cochrane Central Register of Controlled Trials, Google Scholar, and CINAHL. Review Methods The methods were developed in concordance with the Preferred Reporting Items for Systematic Reviews and Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 102 publications
(217 reference statements)
0
14
0
Order By: Relevance
“…19 Barriers to health care access and other disparities among rural populations have been a topic of increasing interest and importance, especially within surgical specialties such as otolaryngology. 8 Of special concern is the potential correlation between reduced health care access and lower quality care and patient outcomes. 8,[20][21][22] In fact, social determinants of health are increasingly shown to have major impacts on the most critical facets of health care such as utilization, quality, and costs, especially in the context of Medicare's Accountable Care Organization models affecting physician reimbursement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Barriers to health care access and other disparities among rural populations have been a topic of increasing interest and importance, especially within surgical specialties such as otolaryngology. 8 Of special concern is the potential correlation between reduced health care access and lower quality care and patient outcomes. 8,[20][21][22] In fact, social determinants of health are increasingly shown to have major impacts on the most critical facets of health care such as utilization, quality, and costs, especially in the context of Medicare's Accountable Care Organization models affecting physician reimbursement.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that regions (usually rural) with lower socioeconomic status, more severe poverty, and lower college graduation rates are also associated with reduced density of specialists, including otolaryngologists 19 . Barriers to health care access and other disparities among rural populations have been a topic of increasing interest and importance, especially within surgical specialties such as otolaryngology 8 . Of special concern is the potential correlation between reduced health care access and lower quality care and patient outcomes 8,20‐22 .…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies comment on socioeconomic status, education, and ethnic disparities, rurality is often left out or briefly addressed. 1 In recent years, Cohn et al conducted 2 studies examining the relationship between maxillofacial trauma patterns and living climate (ie, rural vs urban neighborhoods). 2,3 In another study, rural patients sustained injuries from traffic accidents, sports, violence, and falls.…”
mentioning
confidence: 99%
“…Although these studies comment on socioeconomic status, education, and ethnic disparities, rurality is often left out or briefly addressed. 1…”
mentioning
confidence: 99%
See 1 more Smart Citation